Understanding the relationship between high-density lipoprotein (HDL) subclass distribution and functionality in patients at risk of cardiovascular disease - Woudberg, Nicholas (Department of Medicine, 2018)
Background: Risk factors for cardiovascular disease (CVD) include obesity, ethnicity and hypertension. High-density lipoprotein (HDL) has traditionally served as a marker for CVD risk. Latest studies, however, propose that the composition and subclass distribution and the anti-atherogenic function of HDL are more accurate predictors of CVD risk. We therefore explored whether obesity, ethnicity, exercise and hypertension may modulate HDL composition, subclass and function in three different sample populations of patients affected with these CVD risk factors. Methods: The first study sample population consisted of black and white obese and normal-weight South African women (n=40). In the second sample population, obese black South African women were randomly assigned to exercise (combined aerobic and resistance exercise 4 times/week) or control (sedentary) conditions for 12-weeks (n=32). The third sample population included Nigerian out-patients, divided into healthy controls, hypertensive patients and hypertensive patients with heart failure (HF) (n=80). HDL composition measurements included apolipoproteins A1 and M (ApoA1 and ApoM), paraoxonase (PON1) and platelet activating factor acetylhydrolase (PAF-AH) expression (using Western blotting) and sphingosine-1-phosphate (S1P) content (using mass spectometry). Levels of large, intermediate and small HDL subclasses were measured using the Lipoprint® system. HDL functionality was assessed by measuring PON1 activity, PAF-AH activity, reverse cholesterol efflux capacity, HDL-mediated activation of endothelial nitric oxide synthase (eNOS) and quantification of the expression of vascular cell adhesion molecule in endothelial cells. Results: In all sample populations, HDL-cholesterol concentration was not different between groups. PON1 activity was lower in white compared to black women (0.49±0.09 U/L vs 0.78±0.10 U/L, p<0.05). Obese black women had lower PAF-AH activity compared to obese white women (9.34±1.15 U/L vs 13.89±1.21 U/L, p<0.05). Compared to normal-weight women, obese women had lower large HDL, greater intermediate and small HDL. Compared to the sedentary control condition, exercise training was associated with a decrease in PON1 activity (-8.7±2.4% vs +1.1±3.0%, p<0.05), PAF-AH serum expression (-22.1±8.0% vs +16.9±9.8, p<0.005) and small HDL subclasses (-10.1±5.4% vs +15.7±6.6%, p<0.005). S1P content in HDL was lower in hypertensive and HF patients compared to controls (165 ± 55 vs 201 ± 73 pmol/mg, p < 0.05). HDL subclass distribution was different in hypertensive and HF patients with lower large HDL (48 ± 15 vs 63 ± 7%, p<0.005), higher intermediate (45 ± 7 vs 34 ± 5%, p<0.005) and small HDL (7 ± 9 vs 2 ± 4%, p<0.05). In contrast to HDL from control patients, HDL from all hypertensive patients failed to activate eNOS. Conclusions: In all three sample populations, there were associations between CVD risk factors and measures of HDL quality. HDL subclass distribution differences were associated with obesity and hypertensive heart failure, both in cross-sectional studies and in an exercise intervention study. In African sample populations, consideration of HDL quality rather than total HDL quantity may be a more sensitive marker to assess CVD risk.